Production of Feminized Seeds of High CBD Cannabis sativa L. by Manipulation of Sex Expression and Its Application to Breeding - Flajšman, Marko; Slapnik, Miha; Murovec, Jana (Frontiers in Plant Science, 2021)
The use of the cannabis plant as a source of therapeutic compounds is gaining great importance since restrictions on its growth and use are gradually reduced throughout the world. Intensification of medical (drug type) cannabis production stimulated breeding activities aimed at developing new, improved cultivars with precisely defined, and stable cannabinoid profiles. The effects of several exogenous substances, known to be involved in sex expressions, such as silver thiosulfate (STS), gibberellic acid (GA), and colloidal silver, were analyzed in this study. Various concentrations were tested within 23 different treatments on two high cannabidiol (CBD) breeding populations. Our results showed that spraying whole plants with STS once is more efficient than the application of STS on shoot tips while spraying plants with 0.01% GA and intensive cutting is ineffective in stimulating the production of male flowers. Additionally, spraying whole plants with colloidal silver was also shown to be effective in the induction of male flowers on female plants, since it produced up to 379 male flowers per plant. The viability and fertility of the induced male flowers were confirmed by fluorescein diacetate (FDA) staining of pollen grains, in vitro and in vivo germination tests of pollen, counting the number of seeds developed after hybridization, and evaluating germination rates of developed seeds. Finally, one established protocol was implemented for crossing selected female plants. The cannabinoid profile of the progeny was compared with the profile of the parental population and an improvement in the biochemical profile of the breeding population was confirmed. The progeny had a higher and more uniform total CBD (tCBD) to total tetrahydrocannabinol (tTHC) ratio (up to 29.6; average 21.33 ± 0.39) compared with the original population (up to 18.8; average 7.83 ± 1.03). This is the first comprehensive report on the induction of fertile male flowers on female plants from dioecious medical cannabis (Cannabis sativa L.).